Barrières linguistiques dans l'accès aux soins de santé - Bowen, Sarah (Santé Canada, 2001)

Language barriers in access to health care - Bowen, Sarah (Health Canada, 2001)

Language barriers within the Winnipeg regional health authority. Evidence and implications - Bowen, Sarah (Winnipeg Regional Health Authority, 2004)

Communicative sensitivity in the bilingual healthcare setting: A qualitative study of language awareness - Irvine, Fiona. E.; Roberts, Gwerfyl. W.; Jones, Peter; Spencer, Llinos. H.; Baker, Colin. R.; Williams, Cen (Journal of Advanced Nursing, 2006)
Aim. This paper reports on the second phase of a national study in Wales. The research aimed to assess the level of Welsh language awareness amongst healthcare professionals across Wales, and to identify the factors that enhance language choice within service delivery. Background. The literature suggests that language sensitive healthcare practice is central to ensuring high quality care. However, it is evident that language barriers continue to compromise the quality of care within nursing and other health services. One issue that has received little attention is the level of language awareness that healthcare professionals currently demonstrate. Furthermore the factors that influence language choice for bilingual/multilingual speakers are not well explored in the literature. Methods. The study involved semi-structured interviews with a range of healthcare professionals in acute and community settings across Wales. Using a systematic sampling matrix, a purposeful sample of 83 professionals was selected to participate. Twenty-seven of the respondents were nurses, health visitors and midwives. The interviews focussed on the factors that facilitate or impede language sensitive healthcare practice. All interviews were audiotaped and, using a framework analysis approach, conceptual codes were developed and defined and categories and sub-categories were constructed to create thematic charts. Findings. Three main themes were identified: care enhancement, which focussed on the process and outcome of offering language choice to bilingual patients; organizational issues, which reflected issues relating to the infrastructure of service provision; and training implications, which focused on Welsh language learning in health care. Conclusions. Complex dynamics of language use are in operation within bilingual healthcare settings and organizational as well as individual factors are important in facilitating appropriate language use. Many of the issues highlighted are not peculiar to the Welsh context, but apply to healthcare settings across the world, where other minority languages are in use.

La littérat'ie en santé et les communautés francophones, minoritaires et ethnoculturelles - Kaszap, M.; Zanchetta, M. S. (Lire le monde : les littératies multiples et l'éducation dans les communautés francophones, 2009)

Les services de santé au Canada : une perspective linguistique - Lacroix, Frédéric (L'Action nationale, 2006)

La santé des aînés francophones en milieu minoritaire - services, défis et obstacles - Levesque, Annabel; Rivard, Léonard P. (Collège universitaire de Saint-Boniface, 2005)

Linguistic sensitivity, indigenous peoples and the mental health system in Wales - Madoc‐Jones, Iolo (International Journal of Mental Health Nursing, 2004)
Abstract: This paper presents findings from a pilot research project to explore the significance and availability of mental health services in the medium of Welsh in Wales UK. Based on small‐scale research with Welsh‐speaking mental health service users this article argues that being bilingual can be a significant factor in the complex biopsychosocial matrix that underpins mental health problems amongst Welsh speakers. It also argues that the destructive effects of linguistic oppression and the difficulties of second language communication for mental health service users are such that an appropriate health and social care response in Wales involves providing services in a user's preferred language. Service users’ views about the current state of bilingual service provision in Wales are presented which suggests that insufficient attention is being paid to the linguistic needs of Welsh speakers. Eight principles are proposed for mental health service policy and practice in Wales.

Welsh in the health service: The scope, nature and adequacy of Welsh language provision in the National Health Service in Wales. Consumer Council Wales. - Misell, Andrew (2000)
The Welsh Consumer Council set about defining the consumer interest in language in its 1996 report, Welsh as a Consumer Issue. That report emphasised how and why the opportunities for using the Welsh language be considered from the view of the consumer. In general, service providers are well equipped to look after their own interests – the consumer by comparison is often weak. It is this theme that is picked up in this report – Welsh in the Health Service: The Scope, Nature and Adequacy of Welsh Language Provision in the National Health Service in Wales. While the report recognises that, in many instances, Welsh language service provision is about providing equal opportunities and ensuring a high quality, consumer sensitive service, it also identifies groups for whom service provision in the first language is a clinical necessity. The report concludes that in the case of Welsh-speaking patients, there are instances when they cannot be treated effectively except in their first language, or in both their languages. This is especially true in the case of those receiving speech and language therapy, and for the following key groups: - people with mental health problems. - people with learning disabilities and other special needs. - older people, and - young children. The report contains many recommendations and calls for a fundamental change of approach on the part of the NHS in Wales.
Nombres de pages: 85

The Impact of Communication Challenges on the Delivery of Quality Health Care to Minority Clients & Communities - PEI French Language Health Services Network; Société Santé en français (2007)
pages: 69

Accès aux services de santé et aux services sociaux en anglais au Québec. Rapport de données de base 2005-2006 - Pocock, Joanne (Réseau communautaire de santé et de services sociaux, 2006)

Misinterpretation: Language proficiency, recent immigrants, and global health disparities - Pottie, Kevin (Canadian Family Physician, 2007)
https://pmc.ncbi.nlm.nih.gov/articles/PMC2231483/

Étude de l’impact de déterminants psycho-socio-environnementaux sur la santé physique et mentale des femmes enceintes vivant dans un contexte linguistique et culturel minoritaire - Vaillancourt, Cathy; Lacaze-Masmonteil, Thierry (Francophonies d’Amérique, 2009)
La barrière linguistique réduirait le recours aux services préventifs, l’accès aux services basés sur la communication et augmenterait le recours aux services d’urgence. Les femmes sont particulièrement à risque à cause de leurs besoins accrus de services de santé et de soutien psychosociaux durant la grossesse, l’accouchement et la période du post-partum. Cette étude vise à recueillir de l’information sur les expériences de maternité des femmes francophones (Canadiennes et immigrantes) du Nouveau-Brunswick et de l’Alberta. Les résultats de cette étude seront utilisés pour améliorer les soins de santé et l’accès à l’information pour les femmes enceintes en situation linguistique et culturel minoritaire.